(untitled) (Tempo e Argumento, 2022)
In Colombia, socioeconomic stratification emerged in 1994 as a product of a public policy and a government strategy to identify housing for the payment of public services, however, beyond this initial objective, it has been appropriated by many Colombians as a classification system and social representation. This article aims to analyze how a group of Colombian boys and girls interpret, redefine and understand the nuances and complexities of this notion. It will be shown through ethnographic records (2015-2018) that children build their own ideas about how the stratum originates, operates and reproduces, at the same time, that they use it as a way to make sense of the experience of growing up and live in unequal societies.